Institucionalidad ambiental y gestión de conflictos socioambientales en la región Junín: caso Morococha - Balvín Landeo, Luisabel Elvira (2018)
This research’s objective was to determine the relationship between environmental institutionality and socio-environmental conflict management in the Junín region: Morococha case, as well as the relationship between principles of environmental management and conflict demands, the National System of Environmental Management and conflict management, and the relationship between the National System of Evaluation and Environmental Enforcement and citizen participation. It was developed an applied research, at a descriptive-correlational level, with a non-experimental transversal design and a mixed methodological approach. 20 questionnaires were applied to representatives of institutions with competences in socio-environmental conflicts and of associations participating in the Mesa de Diálogo para el Reasentamiento Poblacional de Morococha; the participant observation and the documentary analysis were the techniques used. The results showed that the environmental institutionality in Perú and its implications at the regional and local levels have not allowed an adequate management of the socio-environmental conflict in Morococha, where the Toromocho mining project is being developed, since a correlation of 0.478, rated as a weak positive one, was found. Also, it must be considered that approximately 62.8 % of social conflicts in Peru are of a socio-environmental nature, according to reports from the Defensoría del Pueblo (March 2019) and more than 10 years of conflict management. In conclusion, the strengthening of environmental institutions is needed for an adequate management and prevention of socio-environmental conflicts, especially the practice of transectoriality as a principle of the National Environmental Policy and an adequate National System of Environmental Management.   DOI: https://doi.org/10.31876/sl.v2i1.8